Multimodal integration of homotopic connectivity and transcriptomic signatures in major depressive disorder with sleep disorder comorbidity - Mingyu Li; Yudan Ding; Yangpan Ou; Huabing Li; Feng Liu; Dongsheng Lv; Ping Li; Bing Lang; Wenbin Guo (BMC Psychiatry)
Abstract Background Major depressive disorder (MDD) affects over 300 million people globally, with sleep disorder (SD) being a common symptom. However, the neural mechanisms underlying this comorbidity remain poorly understood. Specifically, the role of interhemispheric functional connectivity, measured via voxel-mirrored homotopic connectivity (VMHC), in MDD with or without SD has not been systematically explored. This study aimed to identify distinct VMHC patterns in MDD patients with SD and without SD and investigate their genetic correlates. Methods Resting-state functional magnetic resonance imaging (fMRI) was performed in 26 MDD patients with SD (Pa_s), 34 without SD (Pa_ns), and 34 healthy controls (HCs). VMHC analysis compared interhemispheric connectivity across groups, followed by receiver operating characteristic (ROC) analysis to evaluate diagnostic utility. Genetic neuroimaging correlation analysis integrated transcriptomic data from the Allen Human Brain Atlas to identify genes and pathways associated with VMHC alterations. Results Compared to Pa_ns, Pa_s exhibited increased VMHC in the precuneus and postcentral gyrus. Relative to healthy controls, both MDD subgroups showed widespread network dysfunction. ROC analyses confirmed that VMHC in the precuneus and postcentral gyrus effectively distinguished MDD patients with and without SD, indicating diagnostic potential. Additionally, we identified genes related to Pa_s-Pa_ns differences in VMHC values and the associated biological processes and signaling pathways. Conclusions This study reveals distinct VMHC signatures in MDD-SD, emphasizing the critical roles of the default mode and sensorimotor networks in sleep-depression comorbidity. The robust diagnostic performance of precuneus and postcentral gyrus VMHC supports their use as biomarkers for subtype differentiation. Identified genetic pathways offer novel targets for mechanistically informed therapies, advancing personalized interventions for MDD-SD. Clinical trial number Not applicable.